2021
DOI: 10.1007/s00420-021-01765-0
|View full text |Cite
|
Sign up to set email alerts
|

Occupational physical activity, mortality and CHD events in the Italian Longitudinal Study

Abstract: Purpose Several recent studies have suggested a ‘physical activity paradox’ whereby leisure-time physical activity benefits health, but occupational physical activity is harmful. However, other studies imply that occupational physical activity is beneficial. Using data from a nationally representative Italian sample, we investigate if the context, or domain, of physical activity matters for mortality and coronary heart disease (CHD) events. Methods Among 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Furthermore, the Ergo-index of the JEM, which was our measure of OPA, was constructed from many different ergonomic exposures, so that it reflects different dimensions of physical workload, including also awkward postures and repetitiveness, besides high physical effort. These other dimensions may be also relevant in increasing the risk of mortality or CVD, as suggested by the fact that in a previous study on the ILS cohort, in which OPA was assessed through self-reports at baseline based on one question on intensity of physical activity at work, no association was found between high OPA and mortality or coronary heart disease incidence in neither gender (Strippoli et al 2022 ). It is worth noting that in several other studies reporting no association, exposure assessment to OPA was also rather crude, as it was mainly based on one question on the type of job performed (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the Ergo-index of the JEM, which was our measure of OPA, was constructed from many different ergonomic exposures, so that it reflects different dimensions of physical workload, including also awkward postures and repetitiveness, besides high physical effort. These other dimensions may be also relevant in increasing the risk of mortality or CVD, as suggested by the fact that in a previous study on the ILS cohort, in which OPA was assessed through self-reports at baseline based on one question on intensity of physical activity at work, no association was found between high OPA and mortality or coronary heart disease incidence in neither gender (Strippoli et al 2022 ). It is worth noting that in several other studies reporting no association, exposure assessment to OPA was also rather crude, as it was mainly based on one question on the type of job performed (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, two recent large longitudinal studies with thorough adjustment for potential confounders found opposite results: while in a Norwegian study men exposed to high OPA showed significantly higher longevity (Dalene et al 2021 ), in a Danish study both CVD incidence and all-cause mortality were increased for exposure to high OPA (Holtermann et al 2021 ). Other recent studies reported an increased risk of mortality or CVD associated with high OPA in various countries (Martinez-Gomez et al 2022 ; Hermansen et al 2019 ; Wanner et al 2019 ; Quinn et al 2021 ), although several other studies did not find any association (Luo et al 2022 ; Pearce et al 2021 ; Strippoli et al 2022 ; Bonekamp et al 2022 ).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, recent studies have noted that high OPA does not necessarily increase the overall risk of mortality [ 35 ]. It has been noticed that after adjustments for socioeconomic status and other confounding factors, high and moderate OPA could even prolong life expectancy, while with no adjustments, the overall mortality and CVD mortality increased in higher OPA groups [ 17 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…An overall LTPA classification was assigned based on the highest level of activity reported. Further details on the assessment of LTPA in the two cohorts can be found elsewhere [ 34 ].…”
Section: Methodsmentioning
confidence: 99%